2016
DOI: 10.1111/jwas.12284
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation with Butyrate and Polyhydroxybutyrate on the Performance of Pacific White Shrimp in Biofloc Systems

Abstract: This study aimed to evaluate the effects of dietary supplementation with sodium butyrate or polyhydroxybutyrate (PHB) on growth performance, as well as changes in intestinal microbiota and hemato‐immunological parameters, of Litopenaeus vannamei reared under a superintensive biofloc system. Twelve 800‐L tanks were each stocked with 250 shrimp/m3 (3.96 ± 0.04 g mean initial weight) and reared over a 6‐wk period. The basal diet and two test diets supplemented with 2% of each feed additive. At the conclusion of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Silva et al (2014) found that a sodium butyrate addition (5–20 g/kg) in diet reduced intestinal Vibrio counts in L. vannamei than sodium propionate supplementation (5–20 g/kg) in diet. The intestinal bacterial count was decreased in shrimp fed diet containing 20 g/kg sodium butyrate showing lower counts of Vibrio (Silva, Jatobá, et al, 2016). Therefore, it is assumed that the efficiency of butyric acid glycerol esters in the present study was because of high levels of butyric acid release in the intestinal tract of shrimp through optimized free organic acids release by endogenous lipases and esterases.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al (2014) found that a sodium butyrate addition (5–20 g/kg) in diet reduced intestinal Vibrio counts in L. vannamei than sodium propionate supplementation (5–20 g/kg) in diet. The intestinal bacterial count was decreased in shrimp fed diet containing 20 g/kg sodium butyrate showing lower counts of Vibrio (Silva, Jatobá, et al, 2016). Therefore, it is assumed that the efficiency of butyric acid glycerol esters in the present study was because of high levels of butyric acid release in the intestinal tract of shrimp through optimized free organic acids release by endogenous lipases and esterases.…”
Section: Discussionmentioning
confidence: 99%
“…Benzoic acid inclusion in the commercial diet is a simple process in which the original components are not altered. The shrimp that were used throughout the experiment were found to be active during feeding time, consuming the pellets as reported in feeding bioassays with several salts of OAs for Pacific white shrimp (da Silva et al 2013Silva et al , 2016aSilva et al , 2016b.…”
Section: Discussionmentioning
confidence: 99%
“…It was also demonstrated in previous studies that the PHB had inert properties on the intestinal microflora of experimental animals. For instance, Da Silva et al (2016) investigated the effects of dietary butyrate and PHB on the performance of Pacific white shrimp and found that the shrimps fed with a 2% PHB diet did not alter significantly in intestinal bacterial counts. In another research, the intestinal microbiota of Siberian sturgeon larvae fed with PHB enriched Artemia nauplii did not differ concerning the control group (Najdegerami et al, 2015).…”
Section: Discussionmentioning
confidence: 99%